Quando o primeiro passo encontra o mundo lá fora: análise das práticas de desemparedamento com bebês - Santos, Pâmella Eduarda Soares dos (Universidade Federal de São Carlos, 2025)
This study aims to analyze pedagogical “unwalling” practices with infants, as documented in academic articles, in order to understand whether and how such practices promote ruptures in the physical, cultural, and epistemological structures of Early Childhood Education, valuing nature as a curricular matrix. The study confronts the childcare-centered legacy of daycares and the historical invisibility of infants’ pedagogical specificities, which have resulted in a model of spatial and curricular confinement in nurseries. This qualitative bibliographic research used Content Analysis as the procedure for data examination. The discussions and results show that unwalling requires the simultaneity of three interconnected ruptures: Physical, Cultural, and Conceptual, the latter being the driving force of the process as it recognizes the infant as an active subject and nature as a curricular axis. A strong convergence among the studies points to the imperative of reflective teacher education as an enabling condition for sensitive observation and the management of acceptable risk. As a final reflective contribution, it is inferred that unwalling in nursery settings can be understood as the enhancement of physical space into a space of fluidity, shifting its structural rigidity to make it adaptable and permeable to the manifestation of infants’ singularities under teacher mediation.
When the first step meets the outside world: an analysis pedagogical unwalling practices with infants
Keywords: Bebês; Natureza; Desemparedamento; Prática pedagógica; Educação infantil; Infants; Nature; Unwalling; Pedagogical practice; Early childhood education; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade